Utilizing trade market analysis to identify the economic impact of a multiday special event in Miami Beach, Florida. Issue 2 (March 2019) - Beckman, Eric; Traynor, Mark
Many events occur each year in rural and urban communities. Some of these events include sporting events and festivals (music, food/beverage, heritage, and art). Some of these events occur for 1 day, but many of these events occur multiple days and are considered "special events." Determining the positive impact of these special events on local communities is critical to the success of the event and helps to gain local stakeholder approval and acceptance for recurring annual events. The current study surveyed attendees (locals and tourists) at a 5-day special event (festival) in Miami Beach, Florida. Locals and tourists were identified utilizing a new trade market analysis methodology, which was applied to the survey respondents and assessed as a relevant measurement tool for the unique destination. The researchers then estimated the economic impact (using noncasual tourists) to determine the value of the festival to stakeholders in Miami Beach.